THE ROLE OF SUPERVISING JUDGES IN PREVENTING VIOLENCE AGAINST PRISONERS IN CORRECTIONAL INSTITUTIONS: Peran Hakim Pengawas Dalam Mencegah Kekerasan Terhadap Narapidana Di Lembaga Pemasyarakatan - Ratu Arum Ningtyas; Ali Muhammad (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The occurrence of violence in correctional institutions is a form of anomaly in the implementation of legislation. Based on the Corrections Law, it is emphasized that treatment of prisoners must be humane. Violence itself occurs due to many factors, namely lack of supervision from supervising judges. The Supervisory Judge has the duties and functions to ensure optimal implementation of criminal sentences in correctional institutions. This research is normative juridical research related to the role of supervisory judges in correctional institutions based on law in the scope of violence against prisoners while serving their sentences. The conclusion of this research is that the process of implementing observation and supervision has not run optimally so it is unable to contribute to the prevention of violence in prisons. The gap between rules and implementation causes the role of the Supervisory Judge to be suboptimal. The inhibiting factors are the lack of budget and transportation, an unbalanced number of judges and workload, a large number of prisoners, and limited time as an active judge as well as a supervising judge and observer. Even though the role of wasmat judges is quite strategic in efforts to prevent violence if examined normatively, there are still no regulations containing sanctions and setting strict monitoring and observation mechanisms, so that prevention of acts of violence cannot be achieved through supervision and observation of supervisory judges